Aggregated proteins in malignant and benign neoplasms - Zabolotnyi, D.I.; Belousova, A.A.; Zabolotna, D.D.; Savchenko, T.D.; Voroshylova, N.M.; Timchenko, M.D.; Tsvirinko, I.R.; Verevka, S.V. (PH Akademperiodyka, 2023)
Summary. Aim: To evaluate the presence of the aggregated proteins in malignant and benign neoplasms for clarifying the role of impaired protein metabolism in the formation of the altered tissues. Object and Methods: The histological specimens prepared from the operative materials of 196 patients with different forms of malignant and benign neoplasms were stained with Congo red and Thioflavin T and studied under the light and polarization microscope. Results: The various forms of β-stacked protein aggregates (β-SPA) inclusions were detected in amyloids, keloid tissue, benign polyps, and several malignant tumors. Conclusion: The formation of non-functional protein aggregates proves the complex character of the impairment of protein metabolism resulting in local or systemic accumulation of secondary protein toxins results in β-SPA formation as the self-sustaining complex of parametabolic processes. The β-SPA formation is of considerable interest since their properties lead to the impairment of the normal physiological processes in adjacent tissues ensuring the chronic course of the pathology.